Remoción de colorantes sintéticos mediante el proceso Fenton heterogéneo usando Fe2O3 soportado en carbón activado obtenido a partir de residuos de rosas - María Paula Castellanos; Ángela Uscátegui; Jorge Fernández; Aura Marina Pedroza; Carlos Enrique Daza.; Julián Camilo García (Universitas Scientiarum)
To study the removal of dyes:reactive black 5 and crystal violet by the Fenton reaction using Fe2O3-catalysts (0-10% m/m of Fe) supported on activated carbon obtained from rose remnants. The activated carbon was obtained from pyrolysis at 500 °C (1h) followed by activation with NaOH (1:2 wt.). The support was classified using several chemical and physical techniques. Fe-catalysts were synthesized by incipient impregnation. Fenton and adsorption treatments were performed in a batch reactor, concentration of dye of 10 mgL-1, 0.25 mgmL-1 catalyst, pH = 3.7, 20 ± 2 ° C, 750 rpm and atmospheric pressure. The activated carbon used as support showed high basicity, presence of polar groups on the surface, high ash content (22.85%) and oxygen (43.93%) and was mostly of the microporous type with a BET surface area of 520 m2g-1. The maximum discoloration achieved for black reactive 5 was obtained with the catalyst of 3% Fe (98.33%) after 180 min. while for the crystal violet it was obtained with the catalyst of 1% Fe (63.95%) after 180 min. Discoloration by Fenton treatment is dependent on the Fe content, the particle size of the active site and the type of dye. The removal of reactive black 5 reached a maximum at 3% Fe while the crystal violet decreased by increasing Fe content. The treatment proposed in this paper is promising for the removal of synthetic dyes present in contaminated water.